NILAI-NILAI MORAL DALAM FILM BUDI PEKERTI DAN RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SMP - Ratna Wulandari; Nazurty; Ade Bayu Saputra (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to identify and analyze the moral values contained in Budi Pekerti film by Wregas Bhanuteja and explore its relevance in literature learning at junior high school level. This research uses a qualitative approach with the method of literary sociology, which views literary works as a reflection of social reality. The data used are transcripts of dialogue in the Budi Pekerti film obtained through listening techniques and analyzed using the Miles and Huberman model which includes data collection, data reduction, data presentation, and conclusion drawing. The results showed that Budi Pekerti movie contains ten main moral values, namely respect, responsibility, honesty, wisdom, self-discipline, helping, caring for others, cooperation, courage, and democracy. These values are not only moral messages for the audience, but also have relevance to literature learning in junior high schools, especially in the Learning Objective Path (ATP) of phase D of the Indonesian Language Merdeka Curriculum which emphasizes listening, reading, and viewing. Thus, movies can be used as an effective learning medium in instilling moral values and shaping student character.